ANTHROPOPHILOUS REPRESENTATIVES OF BRASSICACEAE BURNETT OF THE NORTHERN TURAN (CONSPECTUS OF SPECIES) - P. V. Vesselova (Труды по прикладной ботанике, генетике и селекции)
In the Northern Turan's flora by the present moment 134 species of Brassicaceae Burnett family were noted. It was revealed that 96 (71.6%) species among them had the anthropophilous nature of distribution. They may be found in the destructed, in a varying degree (from weak to very strong), habitats. At the same time 33 species (34.4%) among 96 revealed species may be concerned to wild relatives of cultivated plants.